2019
DOI: 10.1111/jocs.14376
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, multicenter, randomized, controlled trial evaluating the performance of a novel combination powder vs hemostatic matrix in cardiothoracic operations

Abstract: Aim: This trial compared the hemostatic performance of a novel combination powder (CP) to a control hemostatic matrix (HM) in cardiothoracic operations.Methods: Patients meeting eligibility criteria were enrolled after providing informed consent. Subjects were randomized intraoperatively to receive CP (HEMOBLAST Bellows; Biom'up, France) or HM (FLOSEAL Hemostatic Matrix; Baxter Healthcare Corporation, Hayward, CA). Bleeding was assessed using a clinically validated, quantitative bleeding severity scale. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…As a more recently introduced product, there are fewer clinical reports describing the use of Hemoblast than there are for Surgiflo. However, a small (105 subjects), multicenter, randomized clinical trial of nonemergent cardiothoracic procedures showed that Hemoblast was superior to Floseal Hemostatic Matrix for total TTH, a measure of TTH that includes the time required to prepare the device, at 3 and 5 min [49]. Hemoblast is a ready-to-use powder that does not require mixing of components, thus eliminating preparation time before application as required by Floseal, Surgiflo, and some other commercially available products [19,21,50].…”
Section: Discussionmentioning
confidence: 99%
“…As a more recently introduced product, there are fewer clinical reports describing the use of Hemoblast than there are for Surgiflo. However, a small (105 subjects), multicenter, randomized clinical trial of nonemergent cardiothoracic procedures showed that Hemoblast was superior to Floseal Hemostatic Matrix for total TTH, a measure of TTH that includes the time required to prepare the device, at 3 and 5 min [49]. Hemoblast is a ready-to-use powder that does not require mixing of components, thus eliminating preparation time before application as required by Floseal, Surgiflo, and some other commercially available products [19,21,50].…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous authors have examined the retrospective performance of a powdered hemostatic agent 18 as well as the prospective comparative performance of hemostatic agents including powders in cardiothoracic procedures. 15,[19][20][21][22][23][24][25][26][27][28][29][30] However, to the best of our knowledge, this report presents the first direct comparison of 2 powdered hemostatic agents during cardiac surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In challenging surgical settings, hemostatic agents can be useful adjuncts to the armamentarium available to surgeons for the control of bleeding 8 12 and are known to be useful during cardiothoracic surgical operations. 13 15 Recently, a new powder has been added to the toolbox of available hemostatic agents. 16 This study compares a novel combination powder (CP) hemostatic agent (HEMOBLAST™ Bellows, Biom’Up France SAS, Lyon, France) 16 consisting of porcine collagen, bovine chondroitin sulfate, and human pooled plasma thrombin to an established plant derived, polysaccharide starch powder (PP) hemostatic agent (Arista ™ AH, Becton Dickinson/Bard, Warwick, RI, USA) 17 to assess the usefulness of CP.…”
Section: Introductionmentioning
confidence: 99%
“…After being unpacked, thrombin is dissolved in saline and mixed with the gelatin matrix in a canister. The preparation time required may depend on the users' experience, but the whole process could take up to 3 minutes, [4,5] and in order to respond to massive intraoperative bleeding in a timely manner, TGM must be stored on-site in the operating room instead of in storage.…”
Section: Introductionmentioning
confidence: 99%